Muscling in on TRP channels in vascular smooth muscle cells and cardiomyocytes. (September 2017) - Alonso-Carbajo, Lucía; Kecskes, Miklos; Jacobs, Griet; Pironet, Andy; Syam, Ninda; Talavera, Karel; Vennekens, Rudi
Graphical abstract: Highlights: In this review, we provide an overview of the current knowledge on the expression of TRP channels in vascular smooth muscle and cardiac muscle. We discuss the functional properties and role of TRP channels in physiological and pathophysiological processes in vascular smooth muscle and cardiac muscle. We show that TRP channels are versatile regulators of Ca 2+ signalling in these cells, and that in this way they regulate diverse properties such as contractile force, proliferation, myogenic tone and cell death processes. Abstract: The human TRP protein family comprises a family of 27 cation channels with diverse permeation and gating properties. The common theme is that they are very important regulators of intracellular Ca 2+ signaling in diverse cell types, either by providing a Ca 2+ influx pathway, or by depolarising the membrane potential, which on one hand triggers the activation of voltage-gated Ca 2+ channels, and on the other limits the driving force for Ca 2+ entry. Here we focus on the role of these TRP channels in vascular smooth muscle and cardiac striated muscle. We give an overview of highlights from the recent literature, and highlight the important and diverse roles of TRP channels in the pathophysiology of the cardiovascular system. The discovery of the superfamily of Transient Receptor Potential (TRP) channels has significantly enhanced our knowledge of multiple signal transduction mechanisms in cardiac muscle and vascular smooth muscle cells (VSMC). In recent years, multiple studies have provided evidence for the involvement of these channels, not only in the regulation of contraction, but also in cell proliferation and remodeling in pathological conditions. The mammalian family of TRP cation channels is composed by 28 genes which can be divided into 6 subfamilies groups based on sequence similarity: TRPC (Canonical), TRPM (Melastatin), TRPML (Mucolipins), TRPV (Vanilloid), TRPP (Policystin) and TRPA (Ankyrin-rich protein). Functional TRP channels are believed to form four-unit complexes in the plasma, each of them expressed with six transmembrane domain and intracellular N and C termini. Here we review the current knowledge on the expression of TRP channels in both muscle types, and discuss their functional properties and role in physiological and pathophysiological processes.